Tuvan paroemias of comparative semantics with the component сөс as compared to foreign language material - Zinovieva, Elena I.; Alyoshin, Alexey S. (The New Research of Tuva, 2023)
The article deals with Tuvan proverbs and sayings of comparative semantics, which include the component “сөс” against the background of the Buryat, Russian and Swedish languages. The purpose of the work is a systematic, structural and linguoculturological study of Tuvan proverbs with the semantics of comparison in contrast to foreign language examples in order to identify common and distinctive characteristics. The set goal involves handling the following tasks: identifying a corpus of units under study in Tuvan and languages that serve as a background for the analysis; providing a classification of proverbs according to expressed cultural attitudes and syntactic models; description of value preferences expressed by proverbs; analysis of metaphors and nationally biased units as linguistic means that form a national and cultural image. Despite the fact that comparison is a universal way of cognition, comparison in proverbs with the component under consideration has its own distinctive features in each of the analyzed languages. The differences are manifested in the used syntactic models and the predominance of their certain types. Tuvan proverbs of the analyzed category, as well as Buryat paroemiological units, are characterized by sentences built on the principle of syntactic parallelism. In Swedish paroemias, there is no clearly expressed predominance of any type of models, and in case of Russian, contaminations of different types of models prevail in the corpus of paroemias that we have considered. There are more common cultural attitudes in all four languages. Paroemias of the analyzed languages emphasize the importance of the word in people’s lives, highlight the parameters that determine the significance of words, i.e. their semantic load, truthfulness, accuracy; they indicate that the words should not diverge from the deeds. Differences are observed in particular cultural settings, which may be present in one language and be absent in another (others). Thus, Tuvan proverbs emphasize the role of parental words; Buryat ones signify the importance of words spoken in ancient times; Swedish paroemias indicate the necessity of control and responsibility for what is said. The differences also relate to the number of proverbs expressing the same cultural attitude in the analyzed languages. A conclusion is made about the similarities and differences in the cultural attitudes of the analyzed proverbs in these four languages, the expressed value preferences, the figurative component of the proverbial units, which are reflected in the studied fragment of the proverbial space.